Optical Properties of the Synthesized Cr2S3 Nanoparticles Embedded in Polyvinyl Alcohol - Abdullah, Omed Gh.; A. Tahir, Dana; Saber, Dlear R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
Polyvinyl alcohol (PVA) based nanocomposite, with different concentrations of chromium sulfide Cr2S3 nanoparticles, were prepared by reduction of Cr(NO3)3 and Na2S in an aqueous PVA solution, using the chemical reduction rote, and casting technique. Effect of Cr2S3 nanoparticles on optical parameters such as absorbance, absorption coefficient, refractive index, and extinction coefficient have been investigated using UV-Visible spectroscopy. The study reveals that all these parameters are affected by the Cr2S3 nanoparticles concentration. The study has been also extended to investigate the changes in the optical band gap energies, the band tail width for the samples using Tauc and Urbach relations respectively. The optical energy band gap reduced from (6.17 eV) for pure PVA to (4.14 eV) for 0.04M Cr2S3; while the Urbach tail increased from (0.216 eV) for pure PVA to (0.523 eV) for 0.04M Cr2S3. The significant change of the optical properties of PVA with embedded Cr2S3 nanoparticles suggested their applicabilit in optical devices.